1999
DOI: 10.1037/0022-006x.67.1.19
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital smoking cessation programs: Who responds, who doesn't?

Abstract: This study extends the results of a large randomized clinical trial of a multicomponent in-hospital smoking cessation intervention for general hospitalized smokers by examining subgroups of patients who responded to the intervention. The results, obtained using signal detection analysis, produced 6 subgroups of patients with varying degrees of intervention responsiveness. The subgroup most responsive was marked by 100% confidence to quit smoking at baseline. Among patients with less than 100% confidence, confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 39 publications
4
33
0
Order By: Relevance
“…We are using a nurse to implement the tailored behavioral intervention because evidence supports that nurses increase treatment adherence among hypertensive patients (34) and improve blood pressure control (35)(36)(37)(38)(39)(40). Randomized clinical trials have demonstrated that non-physician clinicians are more effective at bringing hypertensive individuals in concordance with national guideline goals (41)(42)(43)(44)(45).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…We are using a nurse to implement the tailored behavioral intervention because evidence supports that nurses increase treatment adherence among hypertensive patients (34) and improve blood pressure control (35)(36)(37)(38)(39)(40). Randomized clinical trials have demonstrated that non-physician clinicians are more effective at bringing hypertensive individuals in concordance with national guideline goals (41)(42)(43)(44)(45).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The intervention was telephone administered for several reasons. First, non-physician delivered interventions has been found to significantly improve patient outcomes for multiple diseases [13,14,[37][38][39][40][41]. Furthermore, telephone reminders are quite effective in changing patient behavior including improving medication adherence [42], physical activity [43], and enhancing diet adherence [44].…”
Section: Tailored Behavior Self-management Interventionmentioning
confidence: 99%
“…Researchers have shown that confidence to quit smoking has one of the strongest associations with high rates of smoking cessation and lower relapse rates. 25,26 The objectives of this study, therefore, were threefold: (1) to explore the beliefs of South Korean men about the health benefits of smoking cessation; (2) to determine their intentions to quit smoking; and (3) to identify factors associated with their confidence to quit smoking.…”
mentioning
confidence: 99%